Bioremoval of Pb2+ by Aspergillus niger D1RA, A heavy metal-resistant fungus isolated from an illegal gold mining site - RISA NOFIANI; RITA MU’IN; HAFIZAH HAFIZAH; PUJI ARDININGSIH (Society for Indonesian Biodiversity, 2024)
Abstract. Nofiani R, Mu’in R, Hafizah, Ardiningsih P. 2024. Bioremoval of Pb2+ by Aspergillus niger D1RA, A heavy metal-resistant fungus isolated from an illegal gold mining site. Biodiversitas 25: 2504-2511. Heavy metal pollution can cause serious problems for the environment and human health. One of the methods to eliminate this pollution is to use heavy metal-resistant fungi isolated from heavy metal-polluted environments. This study aimed to investigate the ability of heavy metal-resistant fungi to remove Pb2+ in liquid media, Potato Dextrose Broth (PDB). Samples were collected from two locations, namely an abandoned illegal gold mining site and illegal gold mine, Samalantan, Bengkayang District, West Kalimantan, Indonesia. Each sample was inoculated on two different agar media (PDA= Potato Dextrose Agar and MEA= Malt Extract Agar) supplemented with 7.5 ppm HgCl2. All fungal species that grew on the surface media were isolated, identified (based on spore morphology and Internal Transcribed Spacer [ITS]), evaluated (tolerance index [TI] against Hg2+, Pb2+, and Zn2+), and assessed for their bioaccumulation capacity and Pb2+removal efficiency. Four isolates (Aspergillus sp. OK2A, Aspergillus sp. OEA, Aspergillus sp. OEB and OEC) were successfully isolated from the abandoned illegal gold mine, while only one isolate (Aspergillus niger D1RA) was isolated from the illegal gold mining site. On the eighth day of incubation, the high tolerance level of each fungus to various selected metal concentrations was Aspergillus sp. OK2A in 40 ppm HgCl2 and 300 ppm ZnCl2; Aspergillus sp. OEA in 40 ppm HgCl2 and 1,200 ppm ZnCl2; Aspergillus sp. OEB in 800 ppm Pb(NO3)2; OEC in 20 ppm HgCl2; A. niger D1RA in 40 ppm HgCl2, 1,200 ppm Pb(NO3)2, 300 ppm ZnCl2. Only A. niger D1RA showed a high tolerance for three metals and was further analyzed to determine the bioaccumulation capacity and removal efficiency of Pb2+. The best bioaccumulation capacity and removal efficiency of Pb2+ in PDB medium supplemented with 100 ppm Pb(NO3)2 at pH 4 were 237.776 mg/g dried biomass and 93.266 %, respectively. In conclusion, A. niger D1RA has the potential as a bioremediation agent to remediate Pb2+ environments.